Effect of TM (TM=Fe, Mn, Cr) alloying on the high temperature properties and strengthening mechanism of Cf/Al composites. (15th April 2021) - Xu, Zhongguo; Li, Daguang; Wang, Pingping; Jiang, Longtao; Chen, Guoqin; Wu, Gaohui
Abstract: In this paper, the Cf /pure Al composite and the Cf /Al–Fe–Mg–Si composite were prepared by pressure infiltration method, and the microstructure and high temperature mechanical properties of these two kinds of composites were studied. The main interface phase of the Cf /pure Al composite is Al4 C3, while in the Cf /Al–Fe–Mg–Si composite, a new type of Fe-rich phase containing Al, Fe, Mn, Cr, Si and other elements with a body-centered cubic structure calibrated by TEM diffraction pattens is discovered, whose lattice constant is 1.39 nm. Results of high temperature bending tests and researches of microstructure demonstrated that, the bending strength of the Cf /Al–Fe–Mg–Si composite decreased first at room temperature to 200 °C, due to re-dissolution of nano-precipitates. Afterwards, the bending strength increased under the combined action of the stress relaxation mechanism, the crack deflection mechanism and the high temperature strengthening mechanism of the Fe-rich phase at a temperature range in 200 °C–400 °C, and reached about 880 MPa at 400 °C, which demonstrated better high temperature mechanical properties than that of the Cf /pure Al composite. The results indicated that the formation of high-temperature stable precipitates through TM alloying can effectively increase the ultimate service temperature of Cf /Al composites. The work in this paper is of great significance in the design and preparation of Cf /Al composites with excellent high-temperature properties. Graphical abstract: Image 1 Highlights: TM alloying can improve the mechanical properties of Cf /Al composites. TM alloying generates a new Fe-rich phase in the composite. Fe-rich phase is a body-centered cubic structure with a lattice constant of 1.39 nm. Fe-rich phase increases the extreme service temperature of Cf /Al composites. A strategy to improve the high temperature performance is TM alloying.